Strategy of Surgical Management of Peripheral Neuropathy Form of Diabetic Foot Syndrome in Ghana. (24th July 2014) - Rdeini, W. M.; Agbenorku, P.; Mitish, V. A.
Abstract : Introduction. Foot disorders such as ulceration, infection, and gangrene which are often due to diabetes mellitus are some major causes of morbidity and high amputation. Aim. This study aims to use a group of methods for the management of diabetic foot ulcers (DFU) in order to salvage the lower limb so as to reduce the rate of high amputations of the lower extremity. Materials and Methods. A group of different advanced methods for the management of DFU such as sharp debridement of ulcers, application of vacuum therapy, and other forms of reconstructive plastic surgical procedures were used. Data collection was done at 3 different hospitals where the treatments were given. Results. Fifty-four patients with type 2 diabetes mellitus were enrolled in the current study: females n = 37 (68.51%) and males n = 17 (31.49%) with different stages of PEDIS classification. They underwent different methods of surgical management: debridement, vacuum therapy (some constructed from locally used materials), and skin grafting giving good and fast results. Only 4 had below knee amputations. Conclusion. Using advanced surgical wound management including reconstructive plastic surgical procedures, it was possible to reduce the rate of high amputations of the lower limb.